2005
DOI: 10.1016/j.cell.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mule/ARF-BP1, a BH3-Only E3 Ubiquitin Ligase, Catalyzes the Polyubiquitination of Mcl-1 and Regulates Apoptosis

Abstract: The elimination of Mcl-1, an anti-apoptotic Bcl-2 family member, is an early and required step for DNA damage-induced apoptosis. The degradation of Mcl-1 can be blocked by proteasome inhibitors, suggesting a role for the ubiquitin proteasome pathway in apoptosis. Here, we demonstrate that Mcl-1 is ubiquinated at five lysines. Biochemical fractionation of cell extracts allowed us to identify a 482 kDa HECT-domain-containing ubiquitin ligase named Mule (Mcl-1 ubiquitin ligase E3) that is both required and suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
794
4
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(818 citation statements)
references
References 39 publications
(3 reference statements)
18
794
4
2
Order By: Relevance
“…One candidate for such an activity is Mule/ARF-BP1, which has been shown to ubiquitylate Mcl-1, thus tagging Mcl-1 for proteasomal degradation and tipping the balance toward apoptosis. 29 However, we did not find that full-length Mcl-1 accumulates in the presence of proteasomal inhibitors (data not shown). Therefore, the putative ER stress-activated E3 ubiquitin-ligase activity is not likely to be Mule/ARF-BP1 ( Figure 5).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…One candidate for such an activity is Mule/ARF-BP1, which has been shown to ubiquitylate Mcl-1, thus tagging Mcl-1 for proteasomal degradation and tipping the balance toward apoptosis. 29 However, we did not find that full-length Mcl-1 accumulates in the presence of proteasomal inhibitors (data not shown). Therefore, the putative ER stress-activated E3 ubiquitin-ligase activity is not likely to be Mule/ARF-BP1 ( Figure 5).…”
Section: Discussionmentioning
confidence: 66%
“…28 In response to DNA damage, the large Bcl-2 homology domain-only protein Mule/ARF-BP1 was shown to ubiquitylate Mcl-1 -an anti-apoptotic Bcl-2 family member -thereby causing its degradation via the proteasome. 29 Also, the Bcl-2 family members Bcl-2, Mcl-1, and Bfl-1 have been shown to undergo proteasomal degradation when critical serine or threonine residues become dephosphorylated in response to treatment with paclitaxel or TNF. [30][31][32][33][34][35] In these examples, proteasomal activity tips the balance of pro-and anti-apoptotic Bcl-2 family members toward apoptosis, and thereby serves as a mediator of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal sequences of ARF-BP1 (also known as Mule, UREB1, E3 histone , LASU1 and HectH9) possess a HECT domain (4036 -4374) (Adhikary et al, 2005;Chen et al, 2005;Liu et al, 2005;Zhong et al, 2005). ARF-BP1 also contains the ubiquitin-associated domain (UBA, 1318 -54) and a WWE domain (1612 -92).…”
Section: Arf-bp1 a Hect E3 Ubiquitin Ligase Plays An Important Rolementioning
confidence: 99%
“…ARF-BP1/HectH9 is indeed overexpressed in a variety of primary tumour samples (Adhikary et al, 2005;Yoon et al, 2005). In addition, ARF-BP1/Mule recently was reported to ubiquitinate and degrade the anti-apoptotic protein Mcl-1 (Warr et al, 2005;Zhong et al, 2005). The physiologic consequences of degrading both proapoptotic and antiapoptotic proteins remain unclear, although it is possible that ARF-BP1 differentially targets these proteins under different states of cell stress and/or other physiologic conditions.…”
Section: Additional Targets Of Arf-bp1/hecth9mentioning
confidence: 99%
“…Consequently, a number of follow-up studies demonstrated that p14 ARF is capable of affecting both cell cycle control and apoptosis induction in a p53-independent manner as well (Hemmati et al, 2002;Korgaonkar et al, 2002;Yarbrough et al, 2002;Eymin et al, 2003;Rocha et al, 2003;Qi et al, 2004;Hemmati et al, 2005;Normand et al, 2005). Recently, ARF-BP1/mule, an E3 ubiquitin ligase, has been identified as a critical component of the ARF tumor suppressor pathway, as it mediates at least part of the mdm-2/p53-independent regulation of apoptosis sensitivity (Chen et al, 2005a;Zhong et al, 2005). Taken together, these data indicate the INK4a/ARF tumor suppressor pathway involves a much more complex signaling network than initially thought Shmueli and Oren, 2005) and further challenge the paradigm that ARF signaling strictly depends on a functional mdm-2/p53 rheostat.…”
Section: Introductionmentioning
confidence: 99%